Calcium, contraction, and hemodynamic alterations induced by arrhythmogenic drugs in the zebrafish larvae. (10th June 2022) - Salgado-Almario, J; Vicente, M; Molina, Y; Martinez-Sielva, A; Vincent, P; Domingo, B; Llopis, J
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): MCIN/AEI/ 10.13039/501100011033 and "ERDF A way of making Europe" by the European Union Background: Ca2+ ion is pivotal in excitation-contraction coupling. The dysregulation of Ca2+ fluxes is at the core of inherited and acquired arrhythmias. In recent years zebrafish have become an attractive vertebrate model to study heart development, cardiotoxicity, and heart diseases. We recently reported that the transgenic zebrafish line Tg(myl7:Twitch-4) expressing the ratiometric Ca2+ indicator Twitch-4 in the heart, allowed imaging Ca2+ transients (CaT) simultaneously with heart contraction in zebrafish larvae, thus maintaining the physiological mechano-electrical feedback. Purpose: This study aimed to detect subtle disturbances in Ca2+ cycling, contractility, and hemodynamics induced by arrhythmogenic drugs in zebrafish larvae. Methods: We have used the zebrafish transgenic line Tg(myl7:Twitch-4) and a custom software to acquire and analyze fluorescence emission ratio images of the heart. Larvae of 3- and 5-days post-fertilization (dpf) were incubated with arrhythmogenic drugs, and their effects on the systolic and diastolic Ca2+ and the CaT amplitude in the atrium and ventricle were determined. As the ventricular diameter was assessed in the same fluorescence images, a simultaneous, real-time, measurement of contraction correlated with Ca2+ was obtained. The systolic and diastolic areas, measured independently, were used to estimate hemodynamic parameters. Results: Dofetilide caused time-dependent bradycardia and ultimately a 2:1 arrhythmia in 3 and 5 dpf larvae, with an increase in the CaT amplitude. the ejection fraction and the stroke volume increased, but the cardiac output decreased due to the low heart rate (2:1 arrhythmia). The T-type Ca2+ channel antagonist ML218 induced bradycardia and decreased systolic and diastolic Ca2+ levels in 3 dpf larvae, but the CaT amplitude did not change. Interestingly, some larvae (3 out of 14) displayed a progressive lengthening of the time between the start of atrial and ventricular CaT, analogous to increased PR interval of the electrocardiogram, until a ventricular systole failed. This is reminiscent of a second-degree atrioventricular block in humans. At higher ML218 concentration, a 2:1 arrhythmia was observed and increased ventricular CaT amplitude in all larvae. Conclusions: We characterized Ca2+ changes induced by arrhythmogenic drugs and correlated them with contractility and hemodynamic parameters. The zebrafish line Tg(myl7:Twitch-4) allowed investigating drug-induced arrhythmias in this animal model with unprecedented detail. This transgenic line will serve to screen cardiotoxicity during drug development and to study conduction and rhythm defects in zebrafish, and their correlation with human disease.